2022
DOI: 10.1111/ejn.15651
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal development of large‐scale functional brain networks for arithmetic ability from childhood to adolescence

Abstract: Arithmetic ability is an important high‐level cognitive function that requires interaction among multiple brain regions. Previous studies on arithmetic development have focused on task‐induced activation in isolated brain regions or functional connectivity among particular seed regions. However, it remains largely unknown whether and how functional connectivity among large‐scale brain modules contributes to arithmetic development. In the present study, we used a longitudinal sample of task‐based functional mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Using a 2‐year longitudinal design in school‐age children, Wang et al. ( 2022 ) found that the arithmetic task‐induced brain activations within the DMN and fronto‐parietal network showed reduced connection to other nodes and became more segregated over time. Collectively, these results suggested the possible role of DMN in regulating arithmetic processing efficiency.…”
Section: Using Neuroimaging Techniques To Understand Sex/gender Diffe...mentioning
confidence: 99%
“…Using a 2‐year longitudinal design in school‐age children, Wang et al. ( 2022 ) found that the arithmetic task‐induced brain activations within the DMN and fronto‐parietal network showed reduced connection to other nodes and became more segregated over time. Collectively, these results suggested the possible role of DMN in regulating arithmetic processing efficiency.…”
Section: Using Neuroimaging Techniques To Understand Sex/gender Diffe...mentioning
confidence: 99%
“…Resting state networks are already apparent in the infant brain and the DMN is present but weakly connected in young children, with increasing within network connectivity in older children and even greater within network connectivity in adults ( de Bie et al, 2012 ; Fair et al, 2009 ). Though the DMN architecture of children and adolescents resembles that of adults by age 10 with established, but weak core connectivity, the whole brain’s overall connectivity profile continues to change from a regionally-dominant functional architecture to a more distributed network architecture during this developmental window, with increasing functional and structural segregation of brain networks (e.g., DMN, executive control network, salience network) that is thought to reflect specialization of each network ( Baum et al, 2017 ; Fair et al, 2008 ; Fan et al, 2021 ; Sato et al, 2014 ; Sherman et al, 2014 ; Wang et al, 2022 ). Importantly, such changes are not uniform across the brain, as neuroimaging studies have identified significant structural and functional developmental changes to the DMN that varied in strength and direction in different subnetworks of the DMN ( Fan et al, 2021 , Supekar et al, 2010 , Uddin et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the deactivated brain regions, such as the medial prefrontal cortex, posterior cingulate cortex, and angular gyrus, form the default mode network (DMN) that plays a role in internal cognitive processes like arithmetic fact retrieval [24,25]. Importantly, the key brain regions of the above-mentioned four networks not only engage in but also interact to support arithmetic processing [19,26]. For example, a previous developmental fMRI study found strong causal interactions between the SN and FPN regions during a simple addition performance [19].…”
Section: Introductionmentioning
confidence: 99%